Debt buildup and currency vulnerability: Evidence from global markets - Donghyun Park; Arief Ramayandi; Shu Tian (Asian Development Bank (ADB), 2020)
In this study, we examine how public and private debt buildup is related to currency depreciation pressure. Our empirical analysis of a panel dataset of 59 advanced and emerging markets reveals that both private and public debt exacerbate currency vulnerability. However, the evidence of a significant effect on currency depreciation pressure is more robust and consistent for private debt than public debt. Furthermore, we find that excessive private debt buildup can be particularly harmful in emerging markets. In addition, our evidence suggests that greater dependence on external financing exacerbates the impact of debt buildup on currency stress. Overall, the evidence highlights the importance of a comprehensive debt surveillance framework which monitors both public and private debt buildup, especially in emerging markets.
Keywords: E44; E50; F31; G15; 330; currency stress; exchange rate; financial vulnerability; private debt; public debt